Potential Benefits of Crowd-Collaborative Farming in Sustaining Small Scale Dairy Farming Business Performance - Penwell, Mokoena Oratilwe; Sam, Ntuli Thembelihle; Tshepo, Ramarumo; Matshonisa, Seeletse Solly (International Journal of Entrepreneurship and Sustainability Studies, 2023)
The importance of small scale agricultural sustainability is gradually declining in low and middle income economies due to the assortment of changes in agriculture and the environment. Moreover, the high withdrawal of small scale farmers from the market disrupts the direct relationships between producers and consumers, and also puts at risk food security, primarily on the local and regional scale. This paper focuses on optimizing farming activities of the small scale dairy farmers (SSDFs) through crowdsourcing and synergy (CSS) platforms. The methodology for this paper is anchored on the construction of resolve using logic and rationality. This paper points that agricultural outputs are more valuable when delivered by teams because of positive synergies. Moreover, agricultural activities could be optimized through collaborative farming and community supported agriculture as CSS platforms known as crowd-collaborative farming (CCF). CCF could effect increased benefits due to suitability of the crafted member composition, yielding improved local market performance in many settings. Moreover, research on CCF as a tool to develop efficient mechanisms for revenue distribution among the collaborators is necessary. The study further recommends that SSDFs should be trained towards CCF to enhance their production output, especially those experiencing high failures and less returns due to debt erosion. SSDFs they should keep in sync with the consumers.